Виховання толерантного ставлення в учнів початкової школи з різним рівнем психофізичного розвитку - Кайдалова, Галина; Kaidalova, H. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядається проблема виховання толерантності у молодших школярів з різним рівнем психофізичного розвитку. Окрему увагу акцентовано на тому, що кількість дітей з різними видами захворювань щорічно збільшується, в чому і полягає необхідність інклюзивної освіти, наведено основні причини, що заважають її впровадженню на сучасному етапі. Окреслено та коротко охарактеризовано низку правил у питанні морального виховання дітей з різним рівнем психофізичного розвитку у взаємодії учень-вчитель. Звернено увагу на те, що молодших школярів, перш за все, можна зацікавити за допомогою активно - рухового способу діяльності, що представлений у вигляді різноманітних ігор та ігрових елементів. Серед останніх, для прикладу, наведено тренінг, декілька етюдів, ігор та вправ. The article examines the problem of tolerance in primary school children with different levels of mental and physical development. Upbringing in children moral virtues, especially in terms of inclusive education, is complex multistage process that depends on teachers and families. Primary school pupils are perfect for learning the cultural norms and rules of behavior, ability to behave and communicate among people and peers, learn the principles of tolerance, reflected in skill detect respectful attitude to another. We pay special attention to the fact that the number of children with different types of diseases increases every year and what is the need inclusive education. The main reasons that hinder implementation of inclusive education today are counted in the article. We outlined and briefly described a number of rules of moral education children with different levels of mental and physical development in pupil-teacher interaction. We noted that younger pupils, above all, be interested with the active motor mode of activity that represent a variety of games and gaming elements. For example, some etudes, games and exercises are characterized in the article.
Upbringing of tolerance in junior pupils with different levels of mental and physical development
Keywords: толерантність; tolerance; толерантна поведінка; молодші школярі; діти з різним рівнем психофізичного розвитку; гра; вправа; tolerant behavior; junior pupils; children with different levels of mental and physical development; game; exercise